Measurements of stimulated-Raman-scattering-induced tilt in spectral-amplitude-coding optical code-division multiple-access systems - Taqi Al-Qazwini, Zaineb A.; Abdullah, Mohamad Khairuddin; Mokhtar, Makhfudzah (Society of Photo-optical Instrumentation Engineers, 2009)
We measure the stimulated Raman scattering (SRS)-induced tilt in spectral-amplitude-coding optical code-division multiple-access (SAC–OCDMA) systems as a function of system main parameters (transmission distance, power per chip, and number of users) via computer simulations. The results show that SRS-induced tilt significantly increases as transmission distance, power per chip, or number of users grows.